2016
DOI: 10.1007/s10646-016-1715-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of triclosan on embryonic development of Chinese toad, Bufo gargarizans

Abstract: Triclosan (TCS) is commonly used worldwide in a range of personal care and sanitizing products. The aim of this study was to evaluate potential effects of TCS exposure on embryonic development of Bufo gargarizans, an endemic frog species in China. Standard Gosner stage 3 B. gargarizans embryos were exposed to 10 ~ 150 μg/L TCS during embryogenesis. Survival, total length, weight, developmental stage, duration of different embryo stages, malformation, and type II and III deiodinase (D2 and D3) expression were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Similar results were also found in other studies [22]. However, the study reported that D2 expression was downregulated in gargarizans embryos that were exposed to 60 and 150 µg/L triclosan [23]. We analyze that differences of research models may explain the diverse effects of triclosan on deiodinases.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were also found in other studies [22]. However, the study reported that D2 expression was downregulated in gargarizans embryos that were exposed to 60 and 150 µg/L triclosan [23]. We analyze that differences of research models may explain the diverse effects of triclosan on deiodinases.…”
Section: Discussionsupporting
confidence: 85%
“…Chinese toad (Bufo gargarizans) is one of the most common amphibian species and is widely distributed in eastern Asia. In previous studies, B. gargarizans has been used as a test organism in the assessment of the potential toxic effects of aquatic pollutants, including copper (Xia et al 2012;Wang et al 2016), Cr (VI) (Li et al 2018;Yao et al 2019;Yang et al 2020), triclosan (Chai et al 2016b(Chai et al , 2017a, lead (Chai et al 2017b;Yang et al 2019), cadmium (Wu et al 2017a(Wu et al , 2017b, fluoride (Bo et al 2018;Wu et al 2018;Wang et al 2019), nitrate (Wang et al 2015;Xie et al 2019), and spirotetramat (Yin et al 2014). Although the adverse effects of Cr (VI) on B. gargarizans have been explored in previous studies, they mainly focused on the embryonic stage (Li et al 2018), gut microbiota (Yao et al 2019), or liver (Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%